The risks of cancer in older women with BRCA pathogenic variants: How far have we come?. Issue 6 (26th December 2022) - Metcalfe, Kelly A.; Gronwald, Jacek; Tung, Nadine M.; McCuaig, Jeanna M.; Eisen, Andrea; Elser, Christine; Foulkes, William D.; Neuhausen, Susan L.; Senter, Leigha; Moller, Pal; Bordeleau, Louise; Fruscio, Robert; et al.
Abstract: Background: The purpose of this study was to estimate the cumulative risks of all cancers in women from 50 to 75 years of age with a BRCA1 or BRCA2 pathogenic variant. Methods: Participants were women with BRCA1 or BRCA2 pathogenic variants from 85 centers in 16 countries. Women were eligible if they had no cancer before the age of 50 years. Participants completed a baseline questionnaire and follow‐up questionnaires every 2 years. Women were followed from age 50 until a diagnosis of cancer, death, age 75, or last follow‐up. The risk of all cancers combined from age 50 to 75 was estimated using the Kaplan–Meier method. Results: There were 2211 women included (1470 BRCA1 and 742 BRCA2 ). There were 379 cancers diagnosed in the cohort between 50 and 75 years. The actuarial risk of any cancer from age 50 to 75 was 49% for BRCA1 and 43% for BRCA2 . Breast ( n = 186) and ovarian ( n = 45) were the most frequent cancers observed. For women who had both risk‐reducing mastectomy and bilateral salpingo‐oophorectomy before age 50, the risk of developing any cancer between age 50 and 75 was 9%. Conclusion: Women with a BRCA1 or BRCA2 pathogenic variant have a high risk of cancer between the ages of 50 and 75 years and should be counselled appropriately. Abstract : Women with a BRCA1 or BRCA2 pathogenic variant have a high risk of cancer after age 50 and should be counseled appropriately.